Competency Profile of Andalusian Teachers in Digital Security: Evaluation of Device Protection in accordance with the DigComp Framework - Villén Contreras , Rafael; Agreda Montoro, Miriam; Rodríguez Moreno, Javier (Revista Complutense de Educación, 2025)
Introduction: The use of electronic devices connected to the network poses challenges and risks associated with digital security, especially with regard to the protection of the devices. This text aims to know the self-perception of Teaching Digital Competence (CDD) in relation to the protection of devices, in accordance with the European framework DigComp 2.2. Method: 497 teachers from the Andalusian educational system participate during the 2022/23 academic year and a questionnaire on Digital Security Competence is applied, validated by experts. It is a broader instrument that is divided into four dimensions, focusing on the “Device Protection” Dimension, made up of 15 items and which allows us to know the level and competency profile of teachers during the performance of their work. Results: Overall, participants demonstrate strong skills in ensuring “Device Protection.” Significant differences in digital competence related to teaching seniority and hours of training are highlighted, indicating that those with more experience and greater training obtain higher scores. However, variability is observed in responses in relation to the use of tracking software in the event of loss or theft, as well as in the implementation of firewalls in public and work environments. Discussion: In summary, the Andalusian teachers who participate in this study exhibit a favorable disposition regarding security to protect their electronic devices, although they present deficiencies in knowledge, skills and practices associated with the safe and responsible use of these devices when they remain connected to the network.